Retrospective on UI description languages, based on eight years' experience with the User Interface Markup Language (UIML). (2nd May 2008) - Helms, James; Abrams, Marc
In this article, we reflect on the experiences of the project to develop and evolve the User Interface Markup Language (UIML), starting from its origin in 1997. We have two objectives in our discussion. First, we suggest one possible vision of a community of researchers and practitioners working on Open User Interface Description Languages (UIDLs), what they could achieve, and how this can help in the transition to a knowledge society. Second, we relate lessons learned from UIML in the hope that other UIDL researchers may avoid the issues and stumbling blocks we encountered along the way.